2021
DOI: 10.1097/md.0000000000026339
|View full text |Cite
|
Sign up to set email alerts
|

Does a combination treatment of repetitive transcranial magnetic stimulation and occupational therapy improve upper limb muscle paralysis equally in patients with chronic stroke caused by cerebral hemorrhage and infarction?

Abstract: The clinical presentation of stroke is usually more severe in patients with intracerebral hemorrhage (ICH) than in those with cerebral infarction (CI); recovery of stroke-related muscle paralysis is influenced and limited by the type of stroke. To date, many patients have been treated by neurorehabilitation; however, the changes in the recovery of motor paralysis depending on the type of stroke, ICH or CI, have not been established. This study aimed to determine this difference in improvement of upper extremit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…Table 1 provides an overview of included studies, and Figure 3 illustrates the variation in study design, rTMS protocol, time post-stroke and number of sessions across studies. Half of the included studies (13/26), encompassing a large majority of the patient population, were single-arm, non-randomized retrospective or prospective studies (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)36). Eleven studies included a sham-control condition either in a crossover or parallel-group design (16,20,(33)(34)(35)(37)(38)(39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 provides an overview of included studies, and Figure 3 illustrates the variation in study design, rTMS protocol, time post-stroke and number of sessions across studies. Half of the included studies (13/26), encompassing a large majority of the patient population, were single-arm, non-randomized retrospective or prospective studies (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)36). Eleven studies included a sham-control condition either in a crossover or parallel-group design (16,20,(33)(34)(35)(37)(38)(39)(40)(41)(42).…”
Section: Resultsmentioning
confidence: 99%
“…In terms of rTMS protocols, 10 studies used excitatory rTMS (17,21,22,33,34,36,39) or iTBS (18,37,38) targeting ipsilesional M1 (17,18,21,22,34,(36)(37)(38)(39) or ipsilesional S1 (33), with either a single session (18,33,34,36,37,39) or a total of 10 sessions (17,21,22,38) of intervention. A total of 13 studies used inhibitory rTMS over contralesional M1, with a range from 5 up to 30 intervention sessions (19,20,(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)41). Two studies used both inhibitory contralesional, as well as excitatory ipsilesional rTMS over M1 (35,40), and a single study measured the effects of a single session of excitatory contralesional rTMS on M1, dorsal premotor cortex (dPMC), and anterior intraparietal sulcus (aIPS) (16).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After the iTBS intervention, the fALFF value in the right frontal part was reduced, suggesting that iTBS attenuated neuronal activity in the contralateral brain. According to the interhemispheric inhibition theory [ 53 , 54 ], the affected hemisphere is inhibited for a certain period after brain injury, while the healthy hemisphere is excited, a condition that is not conducive to functional recovery after stroke. iTBS acting on the left impaired M1 area can inhibit brain activity in the right medial frontal lobe, and some studies [ 55 , 56 ] have shown that right frontal lobe excitability is closely related to the recovery of language status after stroke.…”
Section: Discussionmentioning
confidence: 99%